Two new species of the genus Mycterothrips from Western Iran (Thysanoptera: Thripidae) - Mirab-Balou, Majid; Shi, Min; Chen, Xue-Xin (Zootaxa, 2011)
Two new species of Mycterothrips Trybom (Thripidae: Thripinae), M. hamedaniensis sp. n. and M. weii sp. n., are described and illustrated from Hamedan province in Western Iran.